Case Report: Local Anesthesia Round Window Plugging and Simultaneous Vibrant Soundbridge Implant for Superior Semicircular Canal Dehiscence - Mignacco, Giulia; Salerni, Lorenzo; Bindi, Ilaria; Monciatti, Giovanni; Cerase, Alfonso; Mandalà, Marco (Frontiers in Neurology, 2020)
The aim of the present study is to report the outcomes of round window reinforcement surgery performed with the application of a Vibrant Soundbridge middle ear implant (VSB; MED-EL) in a patient with superior semicircular canal dehiscence (SSCD) who presented with recurrent vertigo, Tullio phenomenon, Hennebert's sign, bone conduction hypersensitivity, and bilateral moderate to severe mixed hearing loss. Vestibular evoked myogenic potentials (VEMPs) and high-resolution computed tomography (HRCT) confirmed bilateral superior semicircular canal dehiscence while this was not seen in magnetic resonance imaging. The surgical procedure was performed in the right ear as it had worse vestibular and auditory symptoms, a poorer hearing threshold, and greatly altered HRCT and VEMPs findings. With local-assisted anesthesia, round window reinforcement surgery (plugging) with perichondrium was performed with simultaneous positioning of a VSB on the round window niche. At the one and 3 months follow-up after surgery, VSB-aided hearing threshold in the right ear improved to mild, and loud sounds did not elicit either dizziness or pain in the patient.